Identification of ship mathematical model parameters for support of automatic control in voyage conditions - Іванов, Сергій Вікторович; Тєут, Василь Михайлович; Олійник, Павло Борисович (Eastern-European Journal of Enterprise Technologies, 2015)
An approach to identifying the ship motion mathematical model and disturbance parameters in voyage conditions is presented in the paper. The approach is intended for use under constraints during the voyage, i.e., under off-course restrictions and during the voyage in the appointed limited-width corridor. To determine the ship model parameters and static disturbance moment value, it was proposed to use spectral analysis of the angular velocity signal. The formulas and test procedure for identifying the model parameters, along with practical recommendations on the approach implementation were given in the paper. The simulation results show that the accuracy of parameters allows to use these data for the autopilot controller synthesis and adjustment. Thus, the rudder deviation angle may be of about one degree, so the ship deviates from the course only by a small angle during the identification process. Tests on the high seas have proved that the proposed approach can be practiced.